Thermoelectric behaviour with high lattice thermal conductivity of Nickel base Ni2CuCrFeAlx (x = 0.5, 1.0, 1.5 and 2.5) high entropy alloys - Kush, Lav; Srivastava, Sanjay; Jaiswal, Yash; Srivastava, Yogesh (Materials research express, 2020)
In this article, investigated Ni-based Ni2CuCrFeAlx (0.5 ≤ x ≤ 2.5) alloys were prepared by powder metallurgy route. On varying x, the alloy changes from single FCC to single BCC with a transition duplex in FCC/BCC region. The severe scattering effect of lattice in these high-entropy alloys was observed by weak x-ray diffraction intensities. Also, owing to this lattice effect, the observed electrical and thermal conductivity are much smaller than those of pure metal components. On a contrary, because of additional scattering effect of FCC/BCC phase boundaries in the alloys, both conductivity values are even higher than those in the duplex phase region. Present work explains the properties of temperature dependant High-Entropy alloys (HEA's) as a potential new class of thermoelectric materials. The thermoelectric properties can be controlled significantly by changing the valence electron concentration via appropriate substitutional elements. Both the electrical and thermal properties were found to decrease with a lower VEC number. These findings highlight the possibility to exploit HEA's as a new class of futuristic high temperature TE materials.